Effects of transcutaneous electric acupoint stimulation on drug use and responses to cue-induced craving: a pilot study - Penetar David M; Burgos-Robles Anthony; Trksak George H; MacLean Robert R; Dunlap Steven; Lee David Y-W; Lukas Scott E (BMC, 2012)
Abstract Background Transcutaneous electric acupoint stimulation (TEAS) avoids the use of needles, and instead delivers a mild electric current at traditional acupoints. This technique has been used for treating heroin addiction, but has not been systematically tested for other drugs of abuse. This study aims to investigate the effects of TEAS on drug addiction. Methods Volunteers who were either cocaine-dependent (n = 9) or cannabis-dependent (n = 11) but were not seeking treatment for their dependence participated in a within-subject, single-blind study. Treatment consisted of twice daily 30-minute sessions of TEAS or sham stimulation for 3.5 days. The active TEAS levels were individually adjusted to produce a distinct twitching response in the fingers, while the sham stimulation involved 2 minutes of stimulation at threshold levels followed by 28 minutes of stimulation below the detection levels. The participants recorded their drug use and drug cravings daily. At 1 hour after the last morning session of TEAS or sham stimulation, a cue-induced craving EEG evaluation was conducted. Event-related P300 potentials (ERPs) were recorded, sorted, and analyzed for specific image types (neutral objects, non-drug-related arousing images, or drug-related images). Results TEAS treatment did not significantly reduce the drug use or drug cravings, or significantly alter the ERP peak voltage or latency to peak response. However, the TEAS treatment did significantly modulate several self-reported measures of mood and anxiety. Conclusion The results of this pilot study with a limited sample size suggest that the acupoint stimulation techniques and protocol used in this trial alone do not significantly reduce cravings for or use of cocaine or cannabis. The findings that TEAS modulates mood and anxiety suggest that TEAS could be used as an adjunct in a multimodal therapy program to treat cocaine and cannabis dependence if confirmed in a full randomized controlled clinical trial.